SAT0444 Incidence and predictors of immunosuppressant discontinuation and risk of subsequent flare in patients with systemic lupus erythematosus. (12th June 2018) - Zen, M.; Saccon, F.; Gatto, M.; Larosa, M.; Iaccarino, L.; Doria, A.
Abstract : Background: Prolonged treatment with immunosuppressants (IS) has been associated with long-term complications in Systemic Lupus Erythematosus (SLE); however, few data on IS discontinuation in remitted patients are available to date. Objectives: We conducted an observational study to describe the proportion of SLE patients who discontinued IS and to assess the potential predictors of a subsequent flare. Methods: We used data from Padua Cohort, which includes 454 SLE patients followed up from 1990 to 2017. Patients treated with IS over the disease course who discontinued IS and seen at least once in 2017 were studied. Reasons for discontinuation were: remission (defined by clinical SLE disease activity Index=0) or poor compliance/intolerance. Flares were defined according to SLEDAI Flare Index. Predictors of a subsequent flare were analysed by multivariate logistic regression analysis. Results: Eligible patients who were ever treated with IS were 297. IS were discontinued in 106 patients (35.7%): mycophenolate (50, 47.2%), azathioprine (27, 25.5%), cyclophosphamide (11, 10.4%), methotrexate (10, 9.4%), cyclosporine (8, 7.5%). Mean ±SD follow-up duration after IS withdrawal was 82±64 months (range 6–320). 83 out of 106 patients (78.4%) discontinued IS due to remission (mean remission duration at IS discontinuation 39±28 months), and 23 (21.6%) due to poor compliance/intolerance. Among remitted patients, 18 (78.3%) experienced a flare after IS discontinuation (9/55 patients with nephritis, 5/10 with arthritis, 2/9 with skin involvement, 1/3 with neuroSLE, 1/4 with haematological involvement) after a mean of 65±52 months (range 6–180). Conversely, in patients with poor compliance/intolerance, 17 relapsed (73.9%) after a mean of 22±16 months. Flare-free 10 year-survival rate was higher in patients who discontinued IS due to remission than to poor compliance/intolerance (p<0.001, figure 1). In patients who discontinued IS due to remission, a shorter duration of remission at IS discontinuation was associated with disease relapse (p=0.006). Patients who were on IS due to nephritis had a lower risk of flare after IS discontinuation compared with patients with other manifestations (16.4% vs 32.1%, OR 0.58, 95% 0.32–0.98, p=0.049); patients with arthritis were those who were more likely to flare (OR 4.61, 95% CI 1.16–18.29, p=0.035). Positive anti-SSA/SSB (OR 0.45, 95% CI 0.26–0.78, p=0.012) and antimalarials intake after IS discontinuation (OR 0.22, 95% CI 0.07–0.73, p=0.015) were associated with a lower risk of flare. No clinical features over the disease course were associated with flare occurrence. At multivariate analysis, antimalarial use was the strongest protective factor against flares after IS discontinuation (OR 0.22, 95% CI 0.05–0.85, p=0.029). Conclusions: In our cohort, one third of patients treated with IS discontinued the drug during the follow-up, in most cases due to a prolonged remission. Patients who discontinued IS due to remission had a higher free-survival rate than those who discontinued these drugs due to poor compliance/intolerance. The use of antimalarials after IS discontinuation was independently associated with a significant decrease in the risk of flare. IS discontinuation in patients with arthritis requires particular caution. Disclosure of Interest: None declared